ACUTE TOXICITY TEST OF SOUR-SOP LEAF EXTRACT AS BIOPESTICIDE - Purnomo, Harsoyo; Utami, Afri (BIOMA, 2011)
ABSTRACT Sour-sop (Annona muricata L) leaf extract is predicted that it can be used as biopes- ticide which is safe to environmental condition. But, toxicity acut test still important to do. The objective of this research is to estimate of the is exposure dose causing 50% mortality (96-h LD50 95% CI) to test orgasnism during 96 h. Toxicity tests with 50 Goldfish (Carassius auratus) were conducted in 20 liters test solution. Five mouthed jar contain 4 liters of test solution with different dose. At least 10 Goldfish weighing 3â5 g were tested at each dose (0 ppm, 12500 ppm, 13250 ppm, 14000 ppm, and 14750 ppm). Toxicity data were analyzed by statistical linear regression with IBM SPSS Statistics 19. The result prediction with regression estimation was obtained logarithmic (log) va-lue scaleÂ interpolation LD50 is 4.142. Transforming (antilog) of this value was obta-ined 96-h LD50 95% CI = 13868 ppm. Conclusion, Sirsak leaf extract can be used as biopesticide with safety limit 1387 ppm. Key words: toxicity, sour-sop leaf extract, LD50, Carassius auratus, biopesticide.